Calculation of dose distributions for 12 106Ru/106Rh ophthalmic applicator models with the PENELOPE Monte Carlo code. Issue 10 (11th September 2013) - Hermida‐López, M.
Abstract : Purpose: : For decades, 106 Ru/ 106 Rh ophthalmic applicators have been widely used to treat intraocular malignancies with good clinical outcomes. Determining the dosimetry of such applicators is challenging because of their spherical shape, the low range of emitted betas and the steep gradients involved. Furthermore, there is a lack of dose distribution data in the literature for some applicator models. It is crucial to understand the generated dose distributions to improve the treatment planning process. This study aims to calculate the dose distributions in water for 12 commercially available 106 Ru/ 106 Rh ophthalmic applicators. Methods: : The applicators were modeled using the Monte Carlo (MC) code PENELOPE‐2008.1. A planar nonclinical applicator was also simulated. Depth‐dose profiles along the central axis and lateral dose profiles at several depths were calculated and compared with the available published measured and calculated data. In the absence of published data, measurements performed by the manufacturer were used. Results: : For some applicators, the calculated results obtained in this work showed improved consistency with the available experimental data compared with previously published calculations. For others, the data calculated in this work represent the first published dose data. Conclusions: : The MC code PENELOPE‐2008.1 can accurately calculate the dose distributions for 106 Ru/ 106 Rh ophthalmic applicators. The obtained set of tabulated dose distribution values may be useful for quality assurance of treatment planning systems and as a reference for comparison with future measurements and calculations.